P10 Risks of low molecular weight Heparin in suspected pulmonary embolism. (2nd December 2011) - Watkins, L; Rafeeq, S; McMullan, N; Stockton, P; Twite, S; Agarwal, S
Abstract : Background: National Patients Safety Agency (NPSA) issued a statement in July 2010 highlighting the risks associated with the prescription of low molecular weight Heparins (LMWHs). Evidence of harm has been reported due to dosing errors caused by failure to weigh patients and calculate creatinine clearance. Aim: We hypothesised that harm associated with prescription of LMWHs is underreported on the national reporting and learning system (NRLS). We performed a retrospective study to evaluate the frequency of harm associated with LMWHs in patients admitted with a suspicion of pulmonary embolism (PE). Results: 70 patients investigated for suspected PE in an acute teaching hospital during September 2010 were reviewed. Mean age 58 years (median 61), 60% female. The majority of patients presented with breathlessness (64%) and pleuritic chest pain (54%). There was no documentation of clinical probability in 69% of notes, however 73% of imaging requests had clinical probability scores recorded. Eight patients (26%) did not have any risk factors for venous thrombo-embolism. Four patients had CT pulmonary angiogram following an inconclusive perfusion scan. The majority of the patients (70%) were weighed prior to prescribing LMWH. Five (7%) patients had their weight estimated and 14 (20%) had no documentation of weight. Creatinine clearance was <30 ml/min in three patients, one patient had their LMWH adjusted accordingly. More than half of patients (53%) received incorrect dose of LMWH. No LMWH related complication was recorded in any patient. Conclusion: This small cross sectional study has limitations. Larger studies are needed to evaluate the frequency of harm associated with incorrect prescription of LMWH.